2022
DOI: 10.3390/ma16010058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Physical and Energetic Properties of Fuel Pellets Made from Sage Waste Biomass with the Addition of Rye Bran

Abstract: The aim of the present study was to evaluate the effect of rye bran addition on the pelleting process of sage waste biomass, and the quality and energetic properties of fuel pellets. The pelleting process was conducted on an SS-4 test stand equipped with a P-300 pelletizer with flat die roller compactors. The addition of 20% rye bran reduced the pelletizer’s power/energy consumption from 3.75 kW/107 kWh t−1 (0% rye bran content) to 3.19 kW/91 kWh t−1, decreased physical and bulk density, and increased the pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…This may be important concerning the potential use of pellets obtained from these raw materials for energy purposes. The increased sulfur and nitrogen content in the fuel are linked to the release of oxides of these elements into the atmosphere during their combustion [45,46]. Comparing the heating value (LHV) for different biomass types, it was found that bakery waste had a comparable heating value to rye straw [47,48], rapeseed straw [46,49], and spruce sawdust [50].…”
Section: Properties Of Raw Materials and Mixturesmentioning
confidence: 99%
“…This may be important concerning the potential use of pellets obtained from these raw materials for energy purposes. The increased sulfur and nitrogen content in the fuel are linked to the release of oxides of these elements into the atmosphere during their combustion [45,46]. Comparing the heating value (LHV) for different biomass types, it was found that bakery waste had a comparable heating value to rye straw [47,48], rapeseed straw [46,49], and spruce sawdust [50].…”
Section: Properties Of Raw Materials and Mixturesmentioning
confidence: 99%
“…More stable pellets were found in Stolarski et al's [62] study, where wood pellets were analyzed and the mechanical durability of coniferous pellets was 99.6 and 97.7%. Also, fuel pellets made from sage waste biomass with the addition of rye bran pellets showed a better mechanical durability index, which was from 97.01 to 98.14% [63]. The resulting corncob lower calorific value was 17.35 ± 0.14 MJ kg −1 , and the ash content was 1.78 ± 0.24%.…”
Section: Discussionmentioning
confidence: 99%
“…The calorific value and the heat of combustion were determined pursuant to PN-EN ISO 1928:2002 and the methodology described previously in publications [28,29].…”
Section: Determination Of Calorific Value and Heat Of Combustionmentioning
confidence: 99%